Variability in pathological characters in Colletotrichum gloeosporioides isolates from custard apple - Y.S. BALGUDE, A.P. GAIKWAD* and (Indian Phytopathology, 2012)
The pathogenic variability of 13 isolates of Colletotrichum gloeosporioides Penz. (Glomerella cingulata) was observed on leaves of 24 varieties of custard apple by attached leaf culture technique. The C. gloeosporioides isolates differed significantly from each other on the basis of pathological attributes viz., latent period, spot size, leaf area infected, disease severity, and virulence index and thus grouped into different virulence categories. Virulence index was positively correlated with virulence and aggressiveness and negatively to the latent period. The analysis of variance for latent period, spot size, aggressiveness, leaf area infected or per cent disease intensity and virulence index showed that the variations in latent period and virulence disease reaction were attributed more to the isolates and aggressiveness to the host varieties than to the isolate x host variety interactions.